Media Frame and Audience Cognitive Bias: Assessing News Effectiveness from a Social Psychological Perspective - Le, Luodan (International Journal of Social Sciences and Public Administration, 2024)
As an important channel of information dissemination, news media plays a key role in shaping public cognition and guiding public opinion. Media frame theory points out that news reports do not reflect reality objectively and neutrally, but construct reality by selecting, emphasizing and excluding specific information. This construction process not only affects the audience’s understanding of the event, but can also lead to cognitive bias. Cognitive bias refers to the distortion or misunderstanding of reality caused by many factors such as prior knowledge, emotional tendency and social norms when individuals process information. From the perspective of social psychology, this paper explores how the media framework affects the audience’s cognitive bias, and analyzes the psychological mechanisms behind it, such as confirmation bias, stereotype, emotional bias and social identity bias. By assessing the effect of news, this paper aims to reveal the complex relationship between the media framework and the audience’s cognitive bias, and propose strategies to reduce the cognitive bias and improve the public media literacy, so as to help the audience understand and evaluate news events more objectively and comprehensively, and promote the healthy development of the information society.